2015
DOI: 10.1007/s10021-014-9833-x
|View full text |Cite
|
Sign up to set email alerts
|

Belowground Ecosystem Recovery During Grassland Restoration: South African Highveld Compared to US Tallgrass Prairie

Abstract: Conversion of cultivated land to grassland is globally practiced to reverse soil degradation, but belowground ecosystem response to restoration has never been compared between old and new world temperate grasslands. We used a chronosequence approach to model change in root biomass and quality (indexed by C:N ratio), microbial biomass and composition [indexed by phospholipid fatty acids (PLFAs)], soil aggregate structure, and soil C and N stocks in the South African Highveld and compared recovery of these varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
(17 reference statements)
2
25
0
Order By: Relevance
“…Zhang et al. (); Baer, Bach, Meyer, Du Preez, and Six (); and Li et al. () reported that tillage is the main initial cause of SOC loss in arable lands.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. (); Baer, Bach, Meyer, Du Preez, and Six (); and Li et al. () reported that tillage is the main initial cause of SOC loss in arable lands.…”
Section: Discussionmentioning
confidence: 99%
“…Different responses of carbon sequestration also appreciated within a time span of 30–40 years (Deng et al, ). Several studies have presented a linear model of SOC accumulation following the cessation of cultivation (McLauchlan et al, ; Deng et al, ), while an asymptotic curve has been reported for the secondary pasture soils in the South African Highveld and US tallgrass prairie (Baer et al, ; Preger et al, ). It is assumed that the surface soil is most affected by land use changes (Guo & Gifford, ; DeGryze et al, ) and after new plantations (Rodrigo Comino et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have estimated the time to restore degraded ecosystems or specific soil characteristics, and have predicted that it would take from 30 yr to more than 200 yr to restore nitrogen, total C or SOC (Baer et al, 2015;Craft et al, 2002), and 16-30 yr to restore SOC, total nitrogen, and phosphorus concentrations in a degraded alkaline grassland in Jilin, China . A synthesis of China's GfGP showed that the C stock tended to stabilize after 30 yr of conversion from cropland (Deng et al, 2014).…”
Section: Predicted Restoration Time Of Soil C Stock and Improvements mentioning
confidence: 99%
“…A synthesis of China's GfGP showed that the C stock tended to stabilize after 30 yr of conversion from cropland (Deng et al, 2014). The studies referred to were based on the assumption that soil characteristics would change at a constant rate using either the best fit exponential model of C changes measured during the history (9-15 yr) of restoration (Baer et al, 2015;Craft et al, 2002;Li et al, 2014) or a linear model for up to 30 yr of history (Deng et al, 2014).…”
Section: Predicted Restoration Time Of Soil C Stock and Improvements mentioning
confidence: 99%
See 1 more Smart Citation